Do commencing nursing and paramedicine students differ in interprofessional learning and practice attitudes: evaluating course, socio-demographic and individual personality effects. Issue 1 (December 2016) - Hallam, Karen; Livesay, Karen; Morda, Romana; Sharples, Jenny; Jones, Andi; de Courten, Maximilian
Abstract Background Interprofessional education (IPE) requires health students to learn with, from and about each other in order to develop a modern workforce with client-centred care at its core. Despite the client centred focus of IPE, training programs often utilize standard approaches across student cohorts without consideration of discipline, sociodemographic and personality variability that attract students to different health disciplines. Knowing the students who engage in IPE to tailor training may prove as beneficial as knowing the client to delivered individualized client centred care in interprofessional practice (IPP). This research investigates whether students commencing undergraduate nursing and paramedicine degrees ener training with existing demographic and personality differences and, if these are associated with different attitudes towards health care teams and interprofessional education. Method This online study recruited 160 nursing and 50 paramedicine students in their first week of their undergraduate course. Students completed questionnaires regarding their background, personality (General Perceived Self Esteem Scale, International Mini Markers) and the attitudes towards health care teams scale (ATHCTS) and interprofessional education perception scale (IEPS). Results Results show that commencing nursing and paramedicine students are demographically different on education, gender, speaking a language other than English at home (LOTE) and their own experience with healthcare. The results further demonstrate that LOTE, discipline being studied and personality factors play a role in perceptions regarding interprofessional training whilst discipline being studied impacted on attitudes towards health care teams in the workforce. Conclusion These results highlight a number of existing personal and psychological differences between individuals who choose to train in these selected professions. This suggests a need for tertiary education IPE programs to move towards tailoring their education to value this student diversity in the same client centred manner that students are asked to develop clinically.